2022
DOI: 10.3390/cancers14081933
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Physical Plasma as Innovative and Tissue-Preserving Therapy for Women Positive for Cervical Intraepithelial Neoplasia

Abstract: (1) Background: Cervical intraepithelial neoplasia (CIN) of long-term persistence or associated with individual treatment indications often requires highly invasive treatments. These are associated with risks of bleeding, infertility, and pregnancy complications. For low- and middle-income countries (LMICs), standard treatment procedures are difficult to implement and manage. We characterized the application of the highly energized gas “noninvasive physical plasma” (NIPP) for tissue devitalization and the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…In addition to these typical CAP sources, some new sources have recently been developed and used in preclinical studies. One example is a non-invasive and non-thermally operated electrosurgical plasma source [ 16 , 17 , 18 ].…”
Section: Cap and Plasma Sourcesmentioning
confidence: 99%
“…In addition to these typical CAP sources, some new sources have recently been developed and used in preclinical studies. One example is a non-invasive and non-thermally operated electrosurgical plasma source [ 16 , 17 , 18 ].…”
Section: Cap and Plasma Sourcesmentioning
confidence: 99%
“…The role of non-surgical therapies, such as RT, topical imiquimod, chemotherapy, photodynamic therapy, and laser CO 2 therapy, remains unclear and can be considered in cases of unresectable, recurrent, and metastatic disease, as well as a valid conservative alternative for non-invasive disease [ 5 , 114 , 115 ]. It is noteworthy that preliminary results indicated that noninvasive physical plasma might be a viable treatment option for women with a cervical intraepithelial neoplasia, and this approach might be explored for VPD patients as well [ 116 ]. The role of RT as an option in the treatment of VPD has not been fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Here, biochemical characterization of lipids as molecular components in human cervical tissue was carried out using Raman spectroscopy. Raman spectroscopy has proven to be a useful technique to identify plasma-dependent changes in the morphology of biological tissue and its molecular components. , Furthermore, modern hyperspectral Raman imaging can now provide faster imaging with high spatial resolution . Mass spectrometry is another widely used method that can be used to detect and image a broad range of low mass metabolite and lipid species (Figure b) .…”
Section: Adapting Current Sensors For Monitoring the Plasma–biologica...mentioning
confidence: 99%